1994
DOI: 10.1148/radiology.192.2.8029397
|View full text |Cite
|
Sign up to set email alerts
|

High-attenuating crescent in abdominal aortic aneurysm wall at CT: a sign of acute or impending rupture.

Abstract: In patients without CT evidence of frank aneurysm leak, the high-attenuating crescent sign should be regarded as a sign of impending AAA rupture, particularly in patients with pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
59
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(60 citation statements)
references
References 0 publications
1
59
0
Order By: Relevance
“…5-8 Unenhanced CT may also identify ruptured TAA, with findings such as aortic aneurysmal change and high-attenuation crescent of the aneurysmal aortic wall. 9 However, there appear to be few studies that have quantified how well AAS can be diagnosed based solely on unenhanced CT images. Therefore, the aim of our Unenhanced CT for Diagnosing AAS that of the delayed phase was 120-180 s. Contrast-enhanced CT scans were reconstructed at 5-mm intervals in the transverse plane, and at 2-mm intervals in the transverse and obliquesagittal planes parallel to the aortic arch in selected cases.…”
Section: Study Populationmentioning
confidence: 99%
“…5-8 Unenhanced CT may also identify ruptured TAA, with findings such as aortic aneurysmal change and high-attenuation crescent of the aneurysmal aortic wall. 9 However, there appear to be few studies that have quantified how well AAS can be diagnosed based solely on unenhanced CT images. Therefore, the aim of our Unenhanced CT for Diagnosing AAS that of the delayed phase was 120-180 s. Contrast-enhanced CT scans were reconstructed at 5-mm intervals in the transverse plane, and at 2-mm intervals in the transverse and obliquesagittal planes parallel to the aortic arch in selected cases.…”
Section: Study Populationmentioning
confidence: 99%
“…It has been reported that thrombus transformation with contrast extravasation into the thrombus and lumen irregularity signify impending rupture (Pillari, Chang et al 1988). Mehard et al reported a significant correlation between impending rupture and high-attenuating crescents in the wall of abdominal aortic aneurysms on unenhanced CT scans (Mehard, Heiken et al 1994). In this retrospective study, the highattenuating crescents were present in 77% of patients with complicated aneurysms, with complications including intramural hematoma, contained rupture, and frank rupture.…”
Section: Imaging For Rupturementioning
confidence: 60%
“…41) Of patients with aneurysms >5 cm, 25-41% were expected to experience an aneurysmal rupture within 5 years. 42) In contrast to the maximal diameter, aneurysmal length was not found to be associated with the risk of rupture.…”
Section: Sizementioning
confidence: 87%